Prospects and Problems of Language Policy - Ahmed Sabi Kazeem; Muritala Imam Suleiman (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
Indigenous languages in Nigeria have been relegated to the background at the expense of foreign languages. Official language policies have variously been enunciated in documents such as the National Policy on Education. Yet, there are problems facing indigenous language is Nigeria. This study examined prospects and problems of language policy to indigenous languages in Nigeria. Scholars and researchers were of the opinion that indigenous languages in Nigeria should incorporate socio-cultural activities. Problems facing the growth and development of indigenous languages were identified and prospects and possible solutions to the identified problems were proffered. It was therefore concluded that despite Nigeria is a multilingual society, there are few multilingual speakers of indigenous languages. It was however recommended that indigenous languages should be developed in order to enhance socio-cultural integration.